DAYA TERIMA DAN INDEKS GLIKEMIK MAKANAN BROWNIES YANG DIPERKAYA TEPUNG BERAS MERAH DAN KURMA - Melissa Ruslan; Annis Catur Adi; Dini Ririn Andrias (Media Gizi Indonesia, 2015)
People with diabetes mellitus need low glycemic index snack to support their nutritional requirement and to control blood glucose levels. The research objective was to analyze the acceptability (color, flavor, texture, and taste) and the glycemic index of brownies enriched with red rice flour (Oryza nivara) and dates (Phoenix dactylivera). Completely randomized factorial design with 5 repetitions was used on 5 formulas, one control formula (F0) and 4 modification formulas; F1 (25% red rice flour and 24% dates), F2 (75% red rice flour and 24% dates), F3 (25% red rice flour and 40% dates), and F4 (75% red rice flour and 40% dates). Four professional panelist and 30 non skilled panelists were recruited. Friedman test and Wilcoxon Sign Rank Test at α=0.05 was used to test the difference between group. Formula F2 has the highest acceptability (color, flavor, texture, and taste) with an average value of 2.83, while the lowest acceptability was found in F3 (25% brown rice flour and 40% of dates) with an average value of 2.40. The glycemic index of brownies formula F2 is 41.97. Brownies F2 which substitute wheat flour with red rice flour (25%:75%) and enriched with dates (24%) was the best modification brownies formula for its color, flavor, and texture with glycemic index of 41.97. Adding other ingredients to brownies can be done to improve the taste and lower glycemic index at the best formula (F2),Keywords: brownies, dates, glycemic index, red rice flour